ADAPTATION AND VALIDATION OF SAFETY ATTITUDE QUESTIONNAIRE AMBULATORY (SAQ-A) IN INDONESIAN PRIMARY HEALTH CARE FACILITIES - Rohmani, Ngatoiatu; Sari, Ike Winahyu (Universitas Muhammadiyah Yogyakarta, 2019)
Prevention of patient safety incidence needs to be pursued by the management committee of healthcare institutions by changing the behavior of healthcare providers to create a patient safety culture. Also, safety culture evaluation needs to be done to assess the implementation of the culture by healthcare providers. For this reason, a valid and reliable instrument is required in order to be accepted and used in Indonesia as a tool to measure of safety culture attitude in healthcare facilities. This study aimed to adopt the Safety Attitude Questionnaire ? Ambulatory (SAQ-A) instrument to Indonesian. The study was carried out in 5 stages, they were: The translation stage, translation result synthesis, back-translated, review of 3 experts to obtain content validity index (CVI) and questionnaires trial which is conducted in 6 Puskesmas, i.e., Puskesmas Pandak I, Puskesmas Pajangan, Puskesmas Godean I, Puskesmas Kalasan, Puskesmas Tempel I and Puskesmas Minggir. Purposive sampling technique was selected to obtain 30 respondents based on inclusion criteria: She/he works in research location and has experience at least for one month, permanent/ contract employee, and not on sabbatical leave or other permission. Data were analyzed using the Content Validity Index (CVI) and Alpha Cronbach Coefficient. The validity test result of the Indonesian version of SAQ-A based on I-CVI and S-CVI was 1.00 with Cronbach?s alpha reliability value from the six dimensions in the questionnaire within range of ? 0.612 ? 0.881. The reliability test result of the full item on the Indonesian version of the SAQ-A questionnaire was ? 0,914. It was concluded that the Indonesian version of the SAQ-A questionnaire is a valid and reliable questionnaire which can be used as a tool to measure safety culture attitudes of healthcare providers in primary healthcare facilities.